The Influence of Principal Leadership, School Culture through Motivation on Junior High School Teacher Performance. - Widiyanti, Erna; Murwati, Murwati; Joko Raharjo, Tri (Educational Management, 2018)
This research aims to describe and to analyse the influence of principal’s leadership, culture of school, through working motivation of the Junior High School teachers in Semarang. The research used the quantitative research of correlation with facto ex-post design. Data collection used questionnaire while analysis technique used validity, reliability, and band analyse (path analysis). The result of research shows that there is direct influence of principal’s leadership to teacher’s performance. There is also indirect influence of principal’s leadership to performance of learning through the activity of motivation. There is direct influence of school culture to teacher’s performance. There is indirect influence of school culture to learning performance through activity of motivation. There is direct influence of working motivation to teacher performance. In order to overcome the problems of teacher performance concerned with internal issue, effort from the educational intitution, teacher, and principal is needed by changing the policy program to make-up the quality of education to have efficient and effective leadership, conducting duty delegation which focuses on process of studying and students’ learning result. The next research should prove the leadership of principal, school culture, and working motivation in improving teacher performance.